2014
DOI: 10.1097/mao.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Different Laser Types in Laser-assisted Stapedotomy

Abstract: A total of 383 unique articles were retrieved. Four studies provided direct evidence, whereas all studies carried moderate to high risk of bias. After exclusion of the studies that did not provide direct evidence and/or carried high risk of bias, 2 studies were considered eligible for data extraction. This best available evidence shows a slightly better air-bone gap closure for CO2 laser compared to potassium titanyl phosphate laser, but the clinical relevance is unclear. The risk difference of 28.1% [95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Recently, Kamalski et al [19] conducted a systematic bibliographic search to identify all original articles, comparing hearing outcome between different lasers used for fenestration in stapedotomy: among a total of 383 unique articles, only two studies were considered eligible for data extraction: they showed a slightly better air-bone gap closure for CO 2 laser compared to KTP laser [17] and an even better postoperative ABG closure in favour of CO 2 laser compared to Er-YAG (22.8 vs 33.4) [4]. Sensorineural hearing loss, measured by postoperative bone conduction shift, did not occur in both study groups.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Kamalski et al [19] conducted a systematic bibliographic search to identify all original articles, comparing hearing outcome between different lasers used for fenestration in stapedotomy: among a total of 383 unique articles, only two studies were considered eligible for data extraction: they showed a slightly better air-bone gap closure for CO 2 laser compared to KTP laser [17] and an even better postoperative ABG closure in favour of CO 2 laser compared to Er-YAG (22.8 vs 33.4) [4]. Sensorineural hearing loss, measured by postoperative bone conduction shift, did not occur in both study groups.…”
Section: Discussionmentioning
confidence: 98%
“…Stapedotomy, tympanostomy, and removal of glomus tumors have been documented with use of CO 2 lasers under microscopic guidance, however the combination of the flexible fiber CO 2 laser and a rigid endoscope in transcanal endoscopic ear surgery (TEES) has not been widely reported [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of laser in stapedectomy is increasing gradually, since it causes less damage to the middle and inner ears. 5 6 …”
Section: Introductionmentioning
confidence: 99%